Fournier's Gangrene Complicating Hematologic Malignancies: Literature Review and Treatment Suggestions - Giovanni D'Arena; Giuseppe Pietrantuono; Emilio Buccino; Giancarlo Pacifico; Pellegrino Musto (Mediterranean Journal of Hematology and Infectious Diseases)
Fournier’s gangrene (FG) is a rare but severe necrotizing fasciitis of the external genitalia that may complicate the clinical course of hematologic malignancies and sometimes may be the first sign of the disease. The clinical course of FG is very aggressive and the mortality is still high despite the improvement in its management. Early recognition of FG and prompt appropriate treatment with surgical debridement and administration of antibiotics are the cornerstone of the management of this very severe disease.